Thyroid hormones induce browning of white fat. Issue 2 (February 2017) - Martínez-Sánchez, Noelia; Moreno-Navarrete, José M; Contreras, Cristina; Rial-Pensado, Eva; Fernø, Johan; Nogueiras, Rubén; Diéguez, Carlos; Fernández-Real, José-Manuel; López, Miguel
Abstract : The canonical view about the effect of thyroid hormones (THs) on thermogenesis assumes that the hypothalamus acts merely as a modulator of the sympathetic outflow on brown adipose tissue (BAT). Recent data have challenged that vision by demonstrating that THs act on the ventromedial nucleus of the hypothalamus (VMH) to inhibit AMP-activated protein kinase (AMPK), which regulates the thermogenic program in BAT, leading to increased thermogenesis and weight loss. Current data have shown that in addition to activation of brown fat, the browning of white adipose tissue (WAT) might also be an important thermogenic mechanism. However, the possible central effects of THs on the browning of white fat remain unclear. Here, we show that 3, 3′, 5, 5′ tetraiodothyroxyne (T4 )-induced hyperthyroidism promotes a marked browning of WAT. Of note, central or VMH-specific administration of 3, 3′, 5-triiodothyronine (T3 ) recapitulates that effect. The specific genetic activation of hypothalamic AMPK in the VMH reversed the central effect of T3 on browning. Finally, we also showed that the expression of browning genes in human WAT correlates with serum T4 . Overall, these data indicate that THs induce browning of WAT and that this mechanism is mediated via the central effects of THs on energy balance.